Virtual inertia analysis of photovoltaic energy storage systems based on reduced-order model - Li, Guanyang; Wang, Junfei; Wang, Xuanlin; Zhang, Li (Frontiers in Energy Research, 2023)
The problem of non-ideal inertia of the photovoltaic energy storage system (PVESS) may occur due to unreasonable voltage control parameters. In response to this issue, this paper establishes an equivalent reduced-order model (EROM) for PVESS. This EROM considers the current control loop, voltage control loop and the virtual inertia control loop based on low-pass filter. This low-pass filter can effectively enhance the system’s virtual inertia. Since the output impedance of this EROM can visually reflect the external characteristics of the virtual inertia control loop, it is suitable for inertia analysis of PVESS. Furthermore, the impact of voltage control parameters and low-pass filter bandwidth on the system’s inertia is discussed from the perspective of the frequency response of the output impedance. Finally, the switch model of the PVESS is built on the RT-BOX hardware-in-the-loop experimental platform. The validity of the EROM and theoretical analysis is verified by several sets of experimental results.